Sport Activity Supervisors’ Attitudes Towards Creative Solutions of Sport Clubs’ Administrative Problems in Saudi Arabia - Alhdrami, Waeel (Journal of Physical Education, 2023)
The research aims at identifying sport activity attitudes towards creative solution for sport clubs’ administrative problems in Saudi Arabia. The researchers used the descriptive method on (93) sport activity supervisor as well as (13) sport club. The subjects were (33) supervisors in addition to (10) supervisors as pilot study subjects. The researcher designed a questioner of (25) items seven of which are negative while the other 18 were positive representing the sport activity supervisor’s attitudes towards creative solution of administrative problems. The researcher recommended the necessity of sport activity supervisors to face administrative problems through creative problems as well as forming a strategy for developing administrative performance in sport activity supervisors of Saudi Arabian clubs.